Efektivitas Model Problem Based Learning terhadap Peningkatan Hasil Belajar Matematika Materi Pecahan Fase A - Kasmantoro, Heru; Patonah, Siti; Maryati, Maryati (Universitas Muria Kudus, 2024)
The purpose of this study is to evaluate how well the Problem-Based Learning (PBL) model affects learning results in the phase A fraction material for the second-grade class at SDN Pandeanlamper 03 Semarang. This study falls under the category of quantitative pre-experimental design research. The research design employed the One Group Pretest-Posttest model. The population for this study consisted of all second-grade students, totaling 26 students. Sample selection was conducted using nonprobability sampling techniques, with the second-grade B class chosen as the research sample. Data collection methods included tests, documentation, and observation. The data analysis involved t-tests, Shapiro-Wilk tests, and Wilcoxon tests. The results of this research show that the results of the paired sample statistical t-test show that there is a difference in the average pretest score, namely 60, while the average posttest score is 76. It can be seen that the posttest average of the students' critical thinking ability test scores is greater than the average. pretest average, then Ho is rejected and Ha is accepted. So, there is an average difference between students' pretest and posttest scores before and after using the Problem Based Learning model on the critical thinking abilities of class IV students at SDN Pandeanlamper 03